2023
DOI: 10.3390/w15183213
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Plastic Additive 1-Hydroxycyclohexyl Phenyl Ketone (1-HCHPK) to Freshwater Microcrustaceans in Natural Water

Irina Blinova,
Aljona Lukjanova,
Heiki Vija
et al.

Abstract: Various potentially toxic compounds associated with plastic (e.g., plastic additives) can enter the environment during plastic fragmentation and/or weathering. 1-Hydroxycyclohexyl phenyl ketone (1-HCHPK) is a widely used photoinitiator, e.g., in UV-radiation-curable technologies such as 3D-printing, plastic coatings and construction materials. 1-HCHPK may reach aquatic ecosystems via various waste-flows, including leaching from consumer goods. However, knowledge of its potential environmental hazard is scarce.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The additives used in the manufacture of the PS could not be disclosed by the supplier. Nevertheless, several common plastic additives (Smith and Taylor, 2002;Samadi et al, 2022) have been identified as toxic to D. magna and other aquatic organisms (Thaysen et al, 2018;Schiavo et al, 2021;Song et al, 2021;Blinova et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The additives used in the manufacture of the PS could not be disclosed by the supplier. Nevertheless, several common plastic additives (Smith and Taylor, 2002;Samadi et al, 2022) have been identified as toxic to D. magna and other aquatic organisms (Thaysen et al, 2018;Schiavo et al, 2021;Song et al, 2021;Blinova et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, growth and development were reduced by all the three phthalates, whereas the lipid content of Daphnia increased upon exposure to these substances. Negative effects on the lifespan of D. magna were observed with DBP at both 1 and 10 µm concentrations, and with DEP at 10 µm [125] . Blinova et al demonstrated in a laboratory assay the negative impacts of 1-Hydroxycyclohexyl phenyl ketone (1-HCHPK) on two planktonic organisms, Thamnocephalus platyurus, Daphnia magna, and the benthic organism Heterocypris incongruens.…”
Section: Effects On Freshwater Biotamentioning
confidence: 93%